The effect of mechanical ventilation on respiratory muscle echogenicity in critically ill children: an observational cohort study - Marloes M. Ijland; Jeroen L. M. van Doorn; Axel Beukman; Johannes G. van der Hoeven; Joris Lemson; Leo M. A. Heunks; Jonne Doorduin (BMC Pediatrics)
Abstract Background Respiratory muscle weakness is common in critically ill children. Changes in respiratory muscle structure play pivotal role in the development of weakness. Echogenicity is a non-invasive marker to detect structural changes in skeletal muscles. In this study, we evaluated respiratory muscle echogenicity in critically ill ventilated children at PICU admission compared to a control group and its change over time. Secondary, we explored its association with clinical parameters and outcome. Methods Two cohorts were studied: a secondary analysis of a prospective longitudinal observational cohort study in mechanically ventilated children (n = 32) and a prospective control group (n = 13) for obtaining reference values. Ultrasound images of the diaphragm and expiratory muscles were analysed. Muscle echogenicity, muscle thickness, muscle thickening fraction, clinical parameters (inflammation, fluid balance and protein intake) and clinical outcome measurements (ventilation free days, extubation failure and 28-day mortality) were collected. Results The analysis included 174 diaphragm ultrasounds and 144 expiratory respiratory muscles ultrasounds. Echogenicity at PICU admission was not different from controls; for the diaphragm: 27.3 [20.0–32.0] vs 26.3 [19.3–29.3] (P = 0.488), m. obliquus externus: 32.2 [25.5–37.9] vs 34.0 [28.0–51.3] (P = 0.166), m. obliquus interna: 29.8 [25.8–38.8] vs 33.0 [27.8–39.3] (P = 0.390), m. transversus: 30.0 [20.8–38.8] vs 32.3 [24.7–37.0] (P = 0.762), respectively. There was no increase in respiratory muscle echogenicity after four days of mechanical ventilation, though a substantial interindividual variation existed. No correlation was found between changes in echogenicity and changes in muscle thickness, thickening fraction and echogenicity on day four of mechanical ventilation, or clinical outcome. The intra-observer repeatability of the echogenicity for all the respiratory muscles was excellent (all ≥ 0.97). Conclusion In critically ill children, four days of mechanical ventilation does not result in an increase in respiratory muscle echogenicity. Our findings suggest that short periods of mechanical ventilation with relatively low ventilator setting in moderate critically ill children do not lead to large structural changes in the respiratory muscles.